EVALUASI FASILITAS BAGI PENYANDANG DISABILITAS DI STASIUN YOGYAKARTA - Aisyah Nur Jannah; Prayogo Afang Prayitno; Prima Juanita Romadhona (TEKNISIA, 2021)
Yogyakarta Station is a railway station located in Yogyakarta City. As a transportation mode transfer point, the station must be inclusive for all train passengers, including passengers with disabilities. An inclusive railway station will be accomplished by providing station facilities that accommodate accessibility for passengers with disabilities. This study aims to evaluate the facilities for passengers with disabilities at Yogyakarta Station. By understanding the evaluation, railway operators and governments will create specific improvements that would make the station more inclusive. The facilities are following the Minister of Transportation Regulation Number PM 98 of 2017 concerning Providing Accessibility to Public Transportation Services for Service Users with Special Needs. This study uses the IPA (Importance Performance Analysis) method obtained through observation and questionnaires. The result shows that based on 15 (fifteen) facilities evaluated, all facilities are available in Yogyakarta Station except the guide block to the counters and toilets, information in Braille letters, ticketing counters/special ticketing counters, and information/customer service rooms which accessible easily. In addition, based on the IPA method, improving facilities for passengers with disabilities at Yogyakarta Station should be prioritized for ready-to-use wheelchair facilities, access to and from passengers in multi-story buildings, and toilet access.